Non-invasive ventilation for preoxygenation during prehospital anaesthesia – a prospective observational study - Harry Ljungqvist; Jouni Nurmi (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Preoxygenation is used to prevent hypoxia during anaesthesia and intubation. In a prehospital setting, preoxygenation is usually performed using a non-rebreather mask or a bag-valve-mask. These methods are however not sufficient for some critically ill patients. Non-invasive ventilation (NIV) has been shown to be more effective than other methods for preoxygenation of these patients in a hospital setting. Despite this, the use of NIV for preoxygenation has not been reported in a prehospital setting. The purpose of this study is to describe the prehospital use of, and experience with, NIV as a preoxygenation technique in patients undergoing prehospital emergency anaesthesia (PHEA). Methods In this prospective observational study, we included 42 patients preoxygenated with NIV for PHEA by one Finnish helicopter emergency medical services unit. We gathered data on, among other things, patient characteristics, vital signs, success of preoxygenation, post-intubation complications and mortality. In addition, we conducted a semi-structured survey on experiences of the use of NIV for preoxygenation among the prehospital physicians in the study unit. Descriptive analyses were performed as well as calculating confidence intervals. Results During the study period from October 2022 to May 2023, a total of 115 PHEAs were performed and NIV preoxygenation was used in 42 (n = 42/115, 37%) of these. Preoxygenation using NIV was technically successful in 100% of cases (n = 42/42, 95% CI 92—100). The median (IQR) oxygen saturation at HEMS arrival was 98% (95—99) and preoxygenation with NIV achieved a median (IQR) oxygen saturation post-intubation of 99% (97—100). No complications of hypoxia were documented, and the rate of pneumonia and mortality did not exceed what was expected based on literature. In the survey, 40% (n = 4/10) of physicians reported using NIV routinely for all patients while 60% (n = 6/10) only used it for those considered susceptible to desaturation. Conclusions This study demonstrates that NIV for preoxygenation has been implemented and is frequently used in prehospital settings in Finland, and that the intervention seems technically successful without clear adverse events.